Drainage or Packing of the Sella? Transsphenoidal Surgery for Primary Pituitary Abscess: Report of Two Cases - Soichi Oya; Junichiro Kumai; Taku Shigeno (Case Reports in Medicine)
The detailed surgical procedure of the transsphenoidal surgery for pituitary abscess has scarcely been described previously because it is a very rare clinical entity. The authors reported two cases of primary pituitary abscess. In case 1, the anterior wall of the sella turcica was reconstructed with the vomer bone after irrigating the abscess cavity, but the sella was not packed by fat for fear of the persistent infection by devascularized tissues. This led to the postoperative meningocele, the cerebrospinal fluid leak, and bacterial meningitis despite the successful abscess drainage. In case 2, tight sellar packing and reconstruction of the sellar wall were performed to avoid these postoperative complications, which resulted in complete drainage and uneventful postoperative course. Although accumulation of more cases is obviously needed to establish the definitive surgical technique in pituitary abscess surgery, our experience might suggest that packing of the sella is not impeditive for postoperative sufficient drainage.